2014
DOI: 10.1021/es405168b
|View full text |Cite
|
Sign up to set email alerts
|

Co-precipitation of Radium with Barium and Strontium Sulfate and Its Impact on the Fate of Radium during Treatment of Produced Water from Unconventional Gas Extraction

Abstract: Radium occurs in flowback and produced waters from hydraulic fracturing for unconventional gas extraction along with high concentrations of barium and strontium and elevated salinity. Radium is often removed from this wastewater by co-precipitation with barium or other alkaline earth metals. The distribution equation for Ra in the precipitate is derived from the equilibrium of the lattice replacement reaction (inclusion) between the Ra(2+) ion and the carrier ions (e.g., Ba(2+) and Sr(2+)) in aqueous and solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
140
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(150 citation statements)
references
References 34 publications
4
140
0
1
Order By: Relevance
“…High concentrations of radionuclides and organic compounds found in flowback and produced waters can pose significant difficulties when treating and reusing flowback water. Radionuclide particles can be removed through different treatment processes, such as reverse osmosis, precipitation, or ion exchange, but some percentage of radium will remain in the effluent (Zhang et al, 2014), and these processes will serve to concentrate the radionuclides, which may require disposal of the treatment residuals in specialized facilities.…”
Section: Characterization Of Marcellus Shale Flowback Water 75mentioning
confidence: 99%
See 1 more Smart Citation
“…High concentrations of radionuclides and organic compounds found in flowback and produced waters can pose significant difficulties when treating and reusing flowback water. Radionuclide particles can be removed through different treatment processes, such as reverse osmosis, precipitation, or ion exchange, but some percentage of radium will remain in the effluent (Zhang et al, 2014), and these processes will serve to concentrate the radionuclides, which may require disposal of the treatment residuals in specialized facilities.…”
Section: Characterization Of Marcellus Shale Flowback Water 75mentioning
confidence: 99%
“…Approximately 10-30% of the fracturing fluid will return to the surface as flowback water (EPA, 2012). In addition, naturally occurring salts, radioisotopes, and other elements will appear in flowback water if there is mixing between the fracturing fluid and the brine present in the formation (Alley et al, 2011;Zhang et al, 2014). Other compounds may form due to reactions between the additives and substances within the shale formation (NYSDEC, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In 2011, the Commonwealth of Pennsylvania banned shipments to municipal sewage treatment plants, though industrial chemical waste treatment (CWT) facilities have continued to play a significant role in shale gas waste treatment and disposal [43]. Chemical analysis of effluent discharged from municipal sewage treatment plants in Pennsylvania before and after the Commonwealth's shipment ban found that concentrations of barium, strontium, bromides, chlorides, TDS, and benzene were reduced in the majority of samples after the ban, which suggests that these treatment plants may not have been providing sufficient treatment of shale gas waste [44].…”
Section: Surface Water Quality Impactsmentioning
confidence: 99%
“…Increases in these dissolved solids may damage economically important species such as brook trout [46], and have contributed to observed increases in carcinogenic disinfection by-products (which increase in the presence of bromide) in finished drinking water in the region's cities [45]. Radionuclides from treated flowback and produced water are also accumulating in stream sediments after partial removal by CWTs, raising questions about longrun impacts on human and ecosystem health [43,47].…”
Section: Surface Water Quality Impactsmentioning
confidence: 99%
“…The barite system is also of engineering interest because it contributes to scale formation in oil and gas production and geothermal operation (Bozau et al 2015), desalination, etc. and because of the ability of barite to form solid solutions with contaminants such as radium and lead (Curti et al 2010;FernandezGonzalez et al 2013;Zhang et al 2014). The creation of a barite barrier in the subsurface, for example, could retard transport of contaminants around nuclear waste repositories.…”
Section: Introductionmentioning
confidence: 99%